Role of acoustic radiation force impulse elastography, aminotransferase to platelet ratio index and fibrotest for the assessment of significant fibrosis and cirrhosis in chronic liver disease - Rijhwani, Anurag; Mohanani, Laxmi; Chouhan, Ankit Ranjitsinh; Khatri, Nikunj M. (International Journal of Research in Medical Sciences, 2020)
Background: Accurate grading of hepatic fibrosis is important for the application of appropriate intervening strategy. Liver biopsy is the golden standard of fibrotic grading, however wide clinical application is hindered by its inherent drawbacks. Biomechanical-based ultrasonic elastography has received mass attention. However, several clinical studies found that the sole application of ultrasonic elastography may bring evident errors in diagnosing hepatic fibrosis. It is suggested that a combination of ultrasonic elastography and serum liver functions tests holds the potential to overcome those disadvantages. Aims and objectives was to study the diagnostic accuracy of ultrasonography elastography, APRI, fibrotest for significant fibrosis and cirrhosis in patients with chronic liver disease and established the correlation between ARFI elastography, APRI, Fibrotest in grading of liver fibrosis Methods: Sixty three patients with chronic liver disease were studied. Liver stiffness was evaluated with ARFI elastography. Histologic staging of liver fibrosis served as the reference standard except a very few cirrhotic patients who were graded as cirrhotic on the basis of clinical examination. The required APRI, Fibrotest parameters and relevant clinical history was recorded. Fibrosis stage was assessed according to the METAVIR classification. Results: ARFI, APRI, and Fibrotest demonstrated a significant correlation with the histological stage. According to ARFI and APRI for evaluating fibrotic stages more than F2, ARFI showed an enhanced diagnostic accuracy than APRI. The combined measurement of ARFI and APRI exhibited better accuracy than ARFI alone when evaluating ≥ F2 fibrotic stage that showed significant concordance i.e. 79.3% cases, out of which 69.8% of total cases were correctly diagnosed on comparison with the gold standard. Fibrotest and ARFI elastography show significant concordance in grading of fibrosis i.e. 82.5%. Cases out of which 68.3% of total cases were correctly diagnosed on comparison with the gold standard. Conclusions: APRI, ARFI, and fibrotest are novel tools among non-invasive modalities to rule out significant fibrosis and cirrhosis in patients with chronic liver disease. ARFI with APRI and ARFI with fibrotest showed enhanced diagnostic accuracy than ARFI or APRI or fibrotest alone for significant liver fibrosis.